Enhancing quantum science and technology in South Korea: A strategic investment framework - Shim, Hyungwook; Suh, Minho (International Journal of Innovative Research and Scientific Studies, 2025)
This study identifies investment priorities for the strategic and cost-effective promotion of quantum science and technology, designated by the Korean government as one of its 12 national strategic technologies. To establish these priorities, an Analytic Hierarchy Process (AHP) analysis was conducted to assess the weighted significance of various evaluation factors at multiple levels. Simultaneously, a novel network centrality measure was applied to analyze the interconnections and relative importance of core tasks. The findings indicate that quantum computing holds the highest priority, with an optimal investment sequence of talent development, fundamental research support, and service infrastructure establishment. Furthermore, given the intricate interdependencies among key initiatives, fostering an innovation ecosystem and advancing quantum science and technology should be prioritized to ensure sustainable growth and development.